Tax evasion, tax monitoring expenses and economic growth: an empirical analysis in OECD countries - Chatzimichael, Konstantinos; Kalaitzidakis, Pantelis; Tzouvelekas, Vangelis (My University, 2019)
Using a standard endogenous growth model with public capital accumulation enriched with tax evasion (Roubini and Sala-i-Martin in J Monet Econ 35:275–301, 1995) developed by Kafkalas et al. (Eur Econ Rev 70:438–453, 2014), we provide empirical evidence on the relationship between aggregate output growth, announced tax rate and tax monitoring expenses for a set of 32 OECD countries during the 2000–2007 period. Our results indicate that high announced tax rates above the elasticity of public capital and excess expenses on tax auditing as means of reducing tax evasion are not effective deepening the recession.
Keywords: Statutory tax rate; Tax monitoring; Tax evasion; GDP growth